Data from: Low fitness at low latitudes: wintering in the tropics increases migratory delays and mortality rates in an Arctic breeding shorebird ... - Reneerkens, Jeroen; Versluijs, Tom S.L.; Piersma, Theunis; Alves, Jose; Boorman, Mark; Corse, Colin; Gilg, Olivier; Hallgrimsson, Gunnar; Lang, Johannes; Loos, Bob; Ntiamoa-Baidu, Yaa; Nuoh, Alfred; et al. (Dryad, 2020)
1. Evolutionary theories of seasonal migration generally assume that the costs of longer migrations are balanced by benefits at the non-breeding destinations. 2. We tested, and rejected, the null hypothesis of equal survival and timing of spring migration for High Arctic breeding sanderling Calidris alba using six and eight winter destinations between 55° N and 25° S, respectively. 3. Annual apparent survival was considerably lower for adult birds wintering in tropical West-Africa (Mauritania: 0.74 and Ghana: 0.75) than in three European sites (0.84, 0.84 and 0.87) and in subtropical Namibia (0.85). Moreover, compared with adults, second calendar-year sanderlings in the tropics, but not in Europe, often refrained from migrating north during the first possible breeding season. During northward migration, tropical-wintering sanderlings occurred at their final staging site in Iceland 5-15 days later than birds wintering further north or south. Namibia-wintering sanderlings tracked with solar geolocators only ... : Data on timing of northward migration of Sanderlings (Calidris alba) through Icelanddata_Sanderling.csvR-script used to analyse timing of northward migration of Sanderlings (Calidris alba) through IcelandR script used to analyse timing of northward migration of Sanderlings through Iceland. Explanations can be found in the script and in the accompanying dataset, as well as in the Methods section in the paper.TimingNorthwardMigration_JAE_V4_20190904.RSanderling Calidris alba bill and wing lengths and body mass at non-breeding areas at various latitudesThe data file contains data of bill and wing lengths and body mass of 2,872 individual Sanderlings (Calidris alba) captured at winter locations between northern Scotland and Namibia. “lat” indicates the average latitude per winter area of capture in decimal degrees, “year” indicates the year of capture. “bill” is the measured bill length in mm, “wing”the wing length in mm and “mass”the body mass in grams. Each row concerns an individual; no individual occurs ...